The relationship between paired associate learning and Chinese word reading in kindergarten children. (12th October 2020) - Liu, Catrina; Chung, Kevin Kien Hoa; Wang, Li‐Chih; Liu, Duo
Abstract : Background: Research has shown that paired associate learning (PAL) plays an important role in children's word reading across different languages. However, little is known about the construct of PAL and its relationship with word reading in Chinese children. Methods: A total of 204 second‐year kindergarten children from Mainland China were assessed on measures of PAL, including the four mapping conditions of PAL: visual–verbal, verbal–verbal, visual–visual and verbal–visual PAL. Tasks of working memory (WM), inhibitory control, visual‐motor integration (VMI), phonological awareness, orthographic knowledge and Chinese word reading were also administered to these children. Results: Our results showed that WM, VMI and phonological awareness were unique predictors of PAL, whereas inhibitory control and orthographic knowledge were not. Furthermore, PAL showed an independent contribution to Chinese word reading after controlling for phonological awareness and orthographic knowledge. The mediation analysis showed that PAL was a significant mediator of the association between different cognitive‐linguistic skills and Chinese word reading. Conclusion: Paired associate learning contributes to Chinese word reading over and above phonological awareness and orthographic knowledge. Findings underscore the potential importance of PAL, as distinct from other cognitive‐linguistic skills, for understanding variability in early reading development. Highlights: What is already known about this topic Studies have shown the significant role of PAL in predicting word reading in Chinese. The association between PAL and word reading has been typically interpreted within the phonological processing framework. What this paper adds PAL is a complex construct that involves a wide range of cognitive‐linguistic skills: working memory (WM), visual‐motor integration and phonological awareness. PAL showed a unique contribution to Chinese word reading after controlling for phonological awareness and orthographic knowledge. PAL was found to be a significant mediator of the association between different cognitive‐linguistic skills and Chinese word reading. Implications for theory, policy or practice PAL may be an important aspect of sound and symbol learning for its relationship with word reading in Chinese, suggesting that PAL is an important contributing factor to word‐level reading development. It is possible that using PAL tasks such as mapping sounds with novel animals and/or characters and word games may promote children's word reading development.